Effectiveness of a Single Fosfomycin Dosage Compared to a Five-Day Ciprofloxacin Course in patients with simple Urinary Tract Infection - MOHAMMAD ALI, SHABANA (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Treating simple diseases like uncomplicated urinary tract infection (UTIs) have become a challenge for physicians due to multi- drug resistance and genetic variations globally as well as in our local population. Aim: To determine the effectiveness of a single fosfomycin (3g) dose in comparison to a 05 daysciprofloxacin (1g)doseamong patients suffering fromuncomplicated urinary tract infection. Methods: This was randomized controlled trial (RCT) with 128 patients enrolled and divided into two groups. Group A received fosfomycin 3mg for 1 day, and group B received ciprofloxacin 1g for 5 days. The data was analyzed in SPSS 25 Version. Results: Patients in group A had an average age of 43.5±9.4 years, while those in group B had an average age of 46.2 ± 7.9. With a statistically significant p-value of 0.028, fosfomycin group A exhibits substantially better efficacy, i.e., 87.5%, than ciprofloxacin group B, i.e., 71.9%.The study compared Fosfomycin and Ciprofloxacin’s efficacy across age groups, marital statuses, and symptoms durations. Fosfomycin was found to be more effective in patients aged 20-40 and married, but not in those aged 40-60, unmarried, or with longer symptoms. Practical Implication: Short duration of medicine, and more effectiveness in treating patients make it better choice for treating UTIs. Conclusion: The outcomes of the Fosfomycin treatment were comparable to those of the ciprofloxacin treatment, even though it was only a single dose course and had better compliance.